2003
DOI: 10.1177/0095327x0303000103
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in the Impact of Military Service on the Socioeconomic Status of Women Veterans

Abstract: W5 [hile women have become increasingly integrated into traditionally male occupations,' it is still unclear what long-term payoffs will accrue to them from their nontraditional work histories. This is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 14 publications
1
38
0
Order By: Relevance
“…The research generally shows that white World War II veterans tends to do better than their non-veteran peers in terms of income and education (Cooney, Segal, Segal, and Falk 2003;Elder and Meguro 1987;Fredland and Little 1985;Martindale and Poston 1979;Sampson and Laub 1996;Teachman and Tedrow 2004;Villemez and Kasarda 1976 States.…”
Section: Generalmentioning
confidence: 99%
See 2 more Smart Citations
“…The research generally shows that white World War II veterans tends to do better than their non-veteran peers in terms of income and education (Cooney, Segal, Segal, and Falk 2003;Elder and Meguro 1987;Fredland and Little 1985;Martindale and Poston 1979;Sampson and Laub 1996;Teachman and Tedrow 2004;Villemez and Kasarda 1976 States.…”
Section: Generalmentioning
confidence: 99%
“…The independence that service members gain from knifing off their pasts may also provide them with the human and cultural capital required to relocate after their service (Sampson and Laub 1996;Xie 1992). Furthermore, service in the military exposes veterans, especially minorities, to mainstream achievement values, working with diverse racial and ethnic groups, and manipulating large-scale bureaucracies (Browning, Lopreato, and Poston 1973;Cooney, Segal, Segal, and Falk 2003). A.R.…”
Section: Theoretical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research on gender extended to the impact of military service on the post-service well-being of women veterans, as part of our extensive research program on the military in the life course (Cooney et al, 2003). We found that among women who served during the volunteer force era and subsequently returned to civilian life, African-American women veterans maintained equivalent socio-economic status to their peers who did not serve.…”
Section: Research On Diversitymentioning
confidence: 83%
“…They did find evidence of a veteran premium among older, pre-AVF veterans, suggesting that military service among "trailblazing" women was relatively advantageous at a time when fewer nonveterans were working, particularly in male-dominated occupations. Cooney et al (2003) also used 1990 Census data, finding that there was no advantage to military service among black women; they showed similar incomes to their nonveteran peers.…”
Section: Prior Research On Female Veterans: Empirical Findingsmentioning
confidence: 99%